2022
DOI: 10.1130/b36297.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between stylolite morphology and the sealing potential of stylolite-bearing carbonate cap rocks

Abstract: We analyzed the sealing effectiveness of cap rocks bearing different types of stylolites using a combination of petrographic, petrophysical, pore structure, and sealing capacity characterization techniques. This study was based on examples of carbonate cap rocks that seal ultradeep hydrocarbon reservoirs of the Tarim Basin (China). Samples from both drill cores and their outcrop analogues were investigated to quantify how morphology influences the sealing capacity of different types of stylolite-bearing rocks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…5B, 5C, 6A, and 6B), (2) closely spaced and amalgamated S planes forming up to ∼1 cm thick bands of insoluble material (Figs. 8A, 8C, and 8D), which may account for a significant decrease of porosity and permeability (Angevine and Turcotte, 1983;Wu et al, 2023), (3) thrust surfaces also decorated by fault gouge (Figs. 5A and 10A), and (4) the aforementioned low permeability values within the STF deformation zone (Fig.…”
Section: Implications On the Permeability Structure Of Fault Zonesmentioning
confidence: 99%
“…5B, 5C, 6A, and 6B), (2) closely spaced and amalgamated S planes forming up to ∼1 cm thick bands of insoluble material (Figs. 8A, 8C, and 8D), which may account for a significant decrease of porosity and permeability (Angevine and Turcotte, 1983;Wu et al, 2023), (3) thrust surfaces also decorated by fault gouge (Figs. 5A and 10A), and (4) the aforementioned low permeability values within the STF deformation zone (Fig.…”
Section: Implications On the Permeability Structure Of Fault Zonesmentioning
confidence: 99%
“…Previous research revealed that temperature and stress are the key factors influencing the brittle-plastic deformation of gypsum caprock (Liao et al, 2019;Kibikas et al, 2021). Studies on the triaxial stress-strain relationship under conditions of varying stress and ambient temperature have shown that the stress is a direct cause of the brittle-plastic transition of the gypsum caprock (Tong et al, 2019;Liao et al, 2020;Wu et al, 2023). According to theory, when confining pressure increases, the stress drop of the stress-strain curve diminishes, and caprock's capabilities gradually shift from brittleness to brittle-plasticity and then back to plasticity when strain hardening takes place (Liao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%